“Some Account of an Extraordinary Traveller”: Using Virtual Tours to Access Remote Heritage Sites of Inuit Cultural Knowledge - Dawson, Peter; Porter, Cecilia; Gadbois, Denis; Keith, Darren; Hughes, Colleen; Suluk, Luke (Études Inuit Studies, 2018)
The use of panoramic images to transport viewers to remote geographic locations can be traced back to the panorama theatres of nineteenth-century Victorian London. More recently, Google’s World Wonders Project has utilized 360-degree panospheres to capture some of the world’s most famous heritage sites. Using arrows that demarcate a defined path of movement, users can virtually tour these sites by “jumping” from one panosphere to the next. Arvia’juaq National Historic site is located near the community of Arviat. Although the heritage value of the site is highly significant, Arvia’juaq sees few national and international visitors because of its remote location. For a variety of reasons, some local Inuit also find it difficult to regularly visit the site even though it is an important source of cultural identity. In this paper, we explore how panospheres can be used to create interactive virtual tours of heritage sites like Arvia’juaq. Although there are some caveats, we argue that virtual reality (VR) tours are potentially powerful tools for connecting people to heritage sites that might otherwise be inaccessible. This has important implications for raising awareness of polar heritage and its significance to Indigenous people, as well as national and international audiences.